2009
DOI: 10.5539/ibr.v1n2p99
|View full text |Cite
|
Sign up to set email alerts
|

The Fisher Effect in an Emerging Economy: The Case of India

Abstract: The objective of this study is to test the relationship between short-term nominal interest rate and inflation in the context of the Indian financial market. To achieve this objective we perform Augmented Dickey-Fuller unit root test to check for stationarity and thereafter we test for co-integration using the Engle-Granger method and further corroborate the findings of this test with the Johansen-Juselius method. Lastly, we perform the Granger causality test. Monthly data of inflation and nominal short term i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
(10 reference statements)
3
6
0
Order By: Relevance
“…The results to a very great degree indicate that inflation has both short-run and association with interest rates. The findings are in line with past studies such as Panopoulou (2005), Gül and Ekinci (2006), Herwartz and Reimers (2006), Westerlund (2006), Ling et al (2008), Sathye, Sharma and Liu (2009), Mahdi and Masood (2011), Ayub et al (2014), Ida & Luguterah (2014), and Jaradat and AI-Hhosban (2014) works that reported of a stable association in a similar study. The findings of a significant long-term link between interest rates and inflation in the current empirical study support the Fisher effect (1930).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results to a very great degree indicate that inflation has both short-run and association with interest rates. The findings are in line with past studies such as Panopoulou (2005), Gül and Ekinci (2006), Herwartz and Reimers (2006), Westerlund (2006), Ling et al (2008), Sathye, Sharma and Liu (2009), Mahdi and Masood (2011), Ayub et al (2014), Ida & Luguterah (2014), and Jaradat and AI-Hhosban (2014) works that reported of a stable association in a similar study. The findings of a significant long-term link between interest rates and inflation in the current empirical study support the Fisher effect (1930).…”
Section: Discussionsupporting
confidence: 92%
“…The research findings in the literature have not been consistent. The findings of these studies are reported in various researchers works (See Wilcox, 1983;Benhabib, Schmitt-Grohe & Uribe, 2002;Berument & Jelassi, 2002;Fahmy & Kandil, 2002;Panopoulou, 2005;Gül & Ekinci, 2006;Herwartz & Reimers, 2006;Westerlund, 2006;Sathye, Sharma, & Liu, 2009;Ayub, Rehman, Iqbal, Zaman, & Atif, 2014;Ida & Luguterah, 2014).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Westerlund (2008) used panel cointegration for 20 OECD countries and found support for the Fisher effect between nominal short-term interest rates and inflation rates. Additionally, Sathye et al (2008) applied the Engle–Granger method for cointegration for India and confirmed the presence of the Fisher effect between inflation rates and yield rates on three-month treasury bills. Piccinino (2011) used cointegration analysis for some European Union member countries and found evidence of the Fisher effect between European interbank interest rates and expected inflation rates.…”
Section: Literature Reviewmentioning
confidence: 68%
“…By using the data on nominal short-term interest rates and inflation rates, he found support for the Fisher effect across countries. Sathye, Sharma and Liu (2008) tested the Fisher effect in India using the Engle-Granger method for cointegration with monthly data from April 1996 till August 2004. By using the data of inflation rate and yield rates on three-month Treasury bills, they confirmed the presence of the Fisher effect in the Indian financial market.…”
Section: Literature Reviewmentioning
confidence: 99%